Pengelolaan Pembelajaran Berbasis Teknologi Informasi:Respon Tenaga Kependidikan terhadap Pembelajaran Daring pada Masa Pandemi Covid-19 di SMKS Yasalam El-Umah Bogor - Maulana Sopian; Nadya Amalia; Lavia Agustriyani; Siti Nur Holisah; Ana Ratnasari (STKIP Muhammadiyah Bogor, 2021)
The impact of the Covid 19 pandemic is very pronounced in the world of education, this has led to changes in the learning system. Efforts to prevent the spread of the virus are being pursued, one of which is by implementing an online learning system. This study aims to determine the management of information technology-based learning. Participants in this study were the principal. This research is a qualitative research, with research instruments, namely interviews and observations. The results of this study illustrate that learning management is carried out in 3 stages, namely (1) planning, (2) implementation, and (3) assessment. In carrying out its role, the principal as a leader in learning is able to manage the entire educational process in the institution, especially in developing the quality of learning during the Covid-19 pandemic by managing information technology-based learning.